Efficiency identity-based threshold group signature scheme - LIU Hong-wei 1; 2; XIE Wei-xin 2; YU Jian-ping 2 (Tongxin xuebao)
Threshold group signature was used to guarantee the security of the collective decision.To improve the efficiency,a new identity-based cryptography threshold group signature scheme was proposed basing on bilinear pairing and secret sharing.In this scheme,the master key was distributed into the whole group and the user’s signature key was stored in a threshold way,these methods ensured the whole security of signature systems.The scheme with a identity-based t-out-of-n secret sharing algorithm was highly-efficient.The careful analysis and the comparison of computational efficiency show that this scheme is secure and efficient.